Kebijakan Luar Negeri Indonesia dalam Sengketa Family Smoking Prevention and Tobacco Control Act: Analisis Two-Level Game Theory - Ismail, Achmad; Keliat, Makmur (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article explains why the Indonesian government did not retaliate the USA according to the DSB WTO authorization, but rather opted to retaliate in the form of signing a mutually agreed solution/MoU in the case of the Family Smoking Prevention and Tobacco Control Act (FSPTCA). FSPTCA was regarded as a discriminatory act issued by the USA against Indonesia’s clove cigarettes. Indonesia responded by disputing it into the Dispute Settlement Body World Trade Organization (DSB WTO). The USA was found guilty because it violated the WTO principle of non-discrimination and so that it was ordered to comply with the Panel and Appellate Body’s recommendation. Indonesia then requested DSB WTO authorization to carry out retaliation. However, Indonesia did not retaliate according to DSB WTO authorization, but rather opted to sign a mutually agreed solution/MoU (Moratorium of Understanding) to end the FSPTCA trade dispute. Using two-level game theory as its analytical framework, this article argued that Indonesia decision to sign a mutually agreed solution instead of retaliation against the USA was driven by the fact that agreement was considered much more significant and suitable to Indonesia interests.